(Nie)zwykłe znaczenie pedagogiki dialogu w teorii nauczania religii - Zellma, Anna (Poznańskie Studia Teologiczne, 2016)
The theory of religious education holds a very important place in the Polish catechetics. It is continuously enriched with new issues, determined by the social and educational situation, that are significant from the point of view of practice. Some of them are integrally interwoven with pedagogy. Such issues include analyses related to the processes of communication between the religious education teacher and the students or to developing a dialogue approach in the participants of the religious education classes. The religious education publications dealing with the above-mentioned problems do not directly include the category of dialogue pedagogy. However, several issues can be perceived as referring to the role of the dialogue understood as the approach and the method in teaching religious instruction. Additionally, the methods of conducting a dialogue between the religious education teacher and the students are repeatedly described. Their analysis leads to the conclusion that issues in the scope of dialogue pedagogy occupy an important place in the theory of religious instruction, since they refer to various dimensions of didactic and educating activity of the religious education instructor and the students. Nevertheless, they require detailed empirical research to determine the (un)usual significance of dialogue pedagogy in practice – in educational interactions between religious education teachers and students.